"Fake News" and Multiple Regimes of "Truth" During the COVID-19 Pandemic in Zimbabwe. Issue 2 (3rd April 2022) - Ncube, Lyton; Mare, Admire
ABSTRACT: Debates around the sociocultural phenomenon known as "fake news" have gathered storm since the 2016 US Presidential elections. Our study problematises the notion of "truth" in a politically polarised and trust-deficit Zimbabwean society, where audiences are balkanised and pigeonholed into predefined filter bubbles. In order to make sense of this phenomenon during the height of the COVID-19 pandemic, we fuse three analytical frameworks—Foucauldian discourse, social construction of the truth and peripheral actors in journalism. This is pertinent in a context where politicians often dismiss news disseminated through mainstream private and social media platforms as "fake". This deployment of the term "fake news" as a (de)legitimation ritual creates the impression that there are certain media organisations whose civic duty is to dispense "authentic" news. Although the government of Zimbabwe presented itself as the "authentic" voice on issues related to COVID-19, inconsistencies were observed through our analysis. The article demonstrates the multiple and systemic layers and structures embedded within the discourse of "fake news" related to the mediation of COVID-19 in Zimbabwe. Our article also argues that the multiple regimes of (non)truth must be understood in the context of power relations between public officials, professional journalists and peripheral actors in journalism.